2009
DOI: 10.1002/ird.502
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and modification of equations for calculating evapotranspiration (ET) with data from Gansu Province, Northwest China

Abstract: A total of 11 empirical evapotranspiration equations were developed by Hargreaves (1975), Hargreaves (1985), Makkink, Turc, Priestley-Taylor, Jensen-Haise, Doorenbos and Pruitt, Abtew, McGuinness and Bordne, Rohwer and Blaney-Criddle. These were compared with pan evaporation data measured at 10 stations in Gansu Province, northwest China. The comparison was first made using the default values in each of the 11 equations, and then redone using calibrated coefficient values. The calibration was made for all 11 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 28 publications
(19 reference statements)
1
10
0
6
Order By: Relevance
“…In Tabari (2010) found that the Makkink model performed well in cold humid climates in contradiction to the findings of this study. Similarly, the conclusion made by Zhai et al (2010) that the Abtew method should be used only at the high plateau regions is in good agreement with the results obtained in this study. Xystrakis and Matzarakis (2011) found equation proposed by Turc (1961) useful on the basis of evaluation of 13 empirical ET 0 equations for Southern Greece, Int.…”
Section: Max | O P |  supporting
confidence: 92%
“…In Tabari (2010) found that the Makkink model performed well in cold humid climates in contradiction to the findings of this study. Similarly, the conclusion made by Zhai et al (2010) that the Abtew method should be used only at the high plateau regions is in good agreement with the results obtained in this study. Xystrakis and Matzarakis (2011) found equation proposed by Turc (1961) useful on the basis of evaluation of 13 empirical ET 0 equations for Southern Greece, Int.…”
Section: Max | O P |  supporting
confidence: 92%
“…While different equations have been tested and calibrated for different regions and sub-regions under different climatic conditions including in Canada [25], in Iran [26] [27] [28], in China [29], in Poland [30], in Florida (USA) [31], in Southeast Australia [32], and in Senegal [3], limited studies were conducted on the adaptability of reference evapotranspiration equation to the African SaheloSaharan region. Therefore, it is critical to assess the adaptability of ETo models and improve them through proper calibration to the local climate conditions.…”
Section: Journal Of Water Resource and Protectionmentioning
confidence: 99%
“…AB method has shown a good mathematical adjustment (R 2 = 0.89) ( Table 5). In a different study, there was a high efficiency of this method in various locations (Zhai et al, 2010). In semi-arid of Iran, Tabari (2010) and R 2 = 0.715) and had a lower efficiency compared to JensH model (RMSE =1.274 mm day -1 and R 2 = 0.734).…”
Section: Solar Radiation-based Methodsmentioning
confidence: 90%
“…However, it was observed that HS had better performance than JensH and Mak methods, which, like AB method, used Rs as one of the input variables. HS, JensH and Mak methods are suitable for arid and semi-arid conditions, according to Todorovic et al (2013), Jensen and Haise (1963) and Makkink (1957), respectively, and AB method for humid conditions (Zhai et al, 2010;Samaras et al, 2014). It is revealed, therefore, that besides input variables, climate plays a crucial role in making a very careful choice of empirical models.…”
Section: Selection Of the Best Empirical Methodsmentioning
confidence: 99%